A critical analysis of the representation of interracial desire in South African cinema: privileging private discourses of desire - Mvusi, Lwazi (My University, 2014)
No abstract provided
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Drama, 2013